2004
DOI: 10.1017/s0265021504007057
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane and propofol influence the expression of apoptosis-regulating proteins after cerebral ischaemia and reperfusion in rats

Abstract: In addition to the anti-necrotic effects of sevoflurane and propofol, these anaesthetics also reduce the concentration of the apoptosis-inducing protein Bax as early as 4 h after ischaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 21 publications
0
20
0
1
Order By: Relevance
“…Der Wirkmechanismus scheint dabei weniger die Reduktion der zerebralen Metabolisierungsrate von Sau erstoff zu sein, sondern die positive Mo dulation pathophysiologischer Kaskaden, die erst durch die Ischämie in Gang ge setzt werden [2, 17,18,34]. In diesem Kon text ist die konsequente Nutzung ausge wählter Anästhetika durchaus sinnvoll, wobei deren Anwendung im Rahmen ei ner multimodalen neuroprotektiven Stra tegie nur als supportive Maßnahme emp fohlen werden kann [19,34].…”
Section: Pharmakologische Neuroprotektionunclassified
“…Der Wirkmechanismus scheint dabei weniger die Reduktion der zerebralen Metabolisierungsrate von Sau erstoff zu sein, sondern die positive Mo dulation pathophysiologischer Kaskaden, die erst durch die Ischämie in Gang ge setzt werden [2, 17,18,34]. In diesem Kon text ist die konsequente Nutzung ausge wählter Anästhetika durchaus sinnvoll, wobei deren Anwendung im Rahmen ei ner multimodalen neuroprotektiven Stra tegie nur als supportive Maßnahme emp fohlen werden kann [19,34].…”
Section: Pharmakologische Neuroprotektionunclassified
“…More recent work by Engelhard and colleagues [18] has shown that, under some circumstances, sustained neuroprotection with volatile agents can be achieved. In a model of hemispheric ischemia combined with hypotension, sevoflurane produced neuroprotection that was apparent even 4 weeks after ischemia.…”
Section: Volatile Anestheticsmentioning
confidence: 99%
“…A closer examination of the models that were employed in these studies indicates that the severity of ischemia determines whether neuroprotection is transient or sustained. In the studies of Engelhard and Sakai, the ischemic insult was either mild [18] or moderate in severity [19 ]. By contrast, the investigations of Kawaguchi, and later by Inoue, all employed a model of severe focal cerebral ischemia.…”
Section: Volatile Anestheticsmentioning
confidence: 99%
“…That antiapoptotic property seems to be partly mediated by its antioxidant effect, i.e. its capacity to inhibit peroxynitrite-mediated apoptosis in astroglia cells [46 ], but also implies an altered expression of apoptosis-regulating proteins such as Bax and Bcl-2 [43,44,47,48 ]. Third, several reports suggest that propofol-based anaesthesia favourably influences the pro versus anti-inflammatory cytokine balance when compared to isoflurane [49,50].…”
Section: Neuroprotectionmentioning
confidence: 99%
“…Its inhibition of NF-kB activation during focal cerebral ischaemia-reperfusion in rats has also been suggested to be one mechanism of neuroprotection [54]. Propofol also increases the ratio of antiapoptotic to proapoptotic proteins which partially mediates the preconditioning effect [43,44,47,48 ].…”
Section: Neuroprotectionmentioning
confidence: 99%